2021
DOI: 10.48550/arxiv.2102.07574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning Model Development from a Software Engineering Perspective: A Systematic Literature Review

Abstract: Data scientists often develop machine learning models to solve a variety of problems in the industry and academy but not without facing several challenges in terms of Model Development. The problems regarding Machine Learning Development involves the fact that such professionals do not realize that they usually perform ad-hoc practices that could be improved by the adoption of activities presented in the Software Engineering Development Lifecycle. Of course, since machine learning systems are different from tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The first group deals with data acquisition and data cleaning, while the second group is dedicated, among others, to training, evaluation, deployment, and monitoring. According to findings in Lorenzoni et al ( 2021 ), a very recent work giving a systematic literature review on the development of machine learning solutions, this process is the most comprehensive and accepted one in the literature.…”
Section: New Approaches and Methodsmentioning
confidence: 99%
“…The first group deals with data acquisition and data cleaning, while the second group is dedicated, among others, to training, evaluation, deployment, and monitoring. According to findings in Lorenzoni et al ( 2021 ), a very recent work giving a systematic literature review on the development of machine learning solutions, this process is the most comprehensive and accepted one in the literature.…”
Section: New Approaches and Methodsmentioning
confidence: 99%
“…Also, there has been a lot of research in this direction. A comprehensive study of the available tools and applications for engineering projects is given by Mentor (Lorenzoni et al, 2021;Meyer, 2001). The study has offered a theoretical framework for understanding the nature and fieldwork of engineering projects.…”
Section: Introductionmentioning
confidence: 99%
“…The software engineering field has widely applied various machine learning (ML) techniques to enhance organizations' efficiency and effectiveness. A recent study (Lorenzoni et al, 2021) revealed that ML models could be employed in different development stages of the software lifecycle, especially in the quality and analytics process. Software quality assurance saves time and money, as it helps developers discover errors and mistakes early in the development process.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, requirements problems, such as insufficient or ambiguous specifications, can cause misunderstandings during the requirement analysis stage. Research reveals that ML could help develop models that can enhance the quality of requirements classification tasks (Lorenzoni et al, 2021). However, selecting and implementing ML techniques to identify ambiguous requirements is not a trivial task.…”
Section: Introductionmentioning
confidence: 99%